2020
DOI: 10.1016/j.eclinm.2020.100466
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic heterogeneity in the prevalence of COVID-19 during lockdown is associated with ethnicity and household size: Results from an observational cohort study

Abstract: Background Accumulating evidence indicates that COVID-19 causes adverse outcomes in ethnic minority groups. However, little is known about the impact of ethnicity and household size on acquiring infection with SARS-CoV-2. Methods We undertook a retrospective cohort study, in Leicester (UK), of all individuals assessed for COVID-19 with polymerase chain reaction (PCR) testing at University Hospitals of Leicester NHS Trust between 1st March and 28th April 2020. We used lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
126
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 33 publications
19
126
0
3
Order By: Relevance
“…A total of 18,728,893 patients from 50 papers were included in the meta-analyses after excluding any missing data within the studies; 14,506,023 (77%) were White; 1,267,802 (7%) were Asian; 527,944 (3%) were Black, 1,578,192 (8%) were Hispanic, 1,113 were Native American, 229,822 (2%) were Mixed, and 617,997(3%) were of Other ethnic group [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , 81] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 18,728,893 patients from 50 papers were included in the meta-analyses after excluding any missing data within the studies; 14,506,023 (77%) were White; 1,267,802 (7%) were Asian; 527,944 (3%) were Black, 1,578,192 (8%) were Hispanic, 1,113 were Native American, 229,822 (2%) were Mixed, and 617,997(3%) were of Other ethnic group [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , 81] .…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 is much more efficiently spread in enclosed and crowded environments [62] . Individuals from ethnic minority backgrounds are more likely to live in larger household sizes comprised of multiple generations [ 26 , 63 ]. They are also more likely to have lower socioeconomic status, which may increase the likelihood of living in overcrowded households, or accommodation with shared facilities or communal areas [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by Darlington, Norman, Ballas, and Exeter (2015) unfolds that while a dissimilarity by health issues are detected, the ethnic incongruity in health is deeply rooted in socioeconomic differences. This can be comprehended in the present context when in their research Martin, Jenkins, Minhas, Gray, Tang, Williams, and Knapp (2020) demonstrated that aggregated documentation reflects, ethnic minority groups are being largely affected by COVID-19 having an increased likelihood of SARS-CoV-2 PCR positivity.…”
Section: Literature Reviewmentioning
confidence: 91%
“…В ряде стран до объявления Всемирной организации здравоохранения (ВОЗ) введены ограничения на перемещения и посещения общественных мест. С начала распространения коронавирусной инфекции системы здравоохранения в разных странах в течение короткого времени переориентировались на оказание ме-дицинской помощи в основном больным COVID-19 (Yu et al 2020, Iqbal et al 2020Martin et al 2020). В основном это выразилось в приостановлении оказания плановой медицинской помощи в стационарных условиях и ограничениях по приёмам в первичном амбулаторном звене.…”
Section: обзор действующих моделей финансирования и мер финансовой поunclassified